Risk factors for bronchial asthma among children in Medina city, Saudi Arabia: an ecological approach - Alahmadi, Alaa; Jradi, Hoda; Alofi, Eyad (International Journal Of Community Medicine And Public Health, 2020)
Background: Asthma is a common disease in Saudi Arabia that affects many individuals. Children are profoundly affected, and the impact of the disease is noticeable in the frequent visits to the emergency departments, missed school days, recurrent hospitalizations, and high death rates. Our study is aimed at identifying the determinant of bronchial asthma risk factors based on the ecological model. Methods: A case-control study was conducted. Samples were randomly selected from two major hospitals in Medina Region, Saudi Arabia, including children aged between 1-14 years. A chi-square test was used to see any differences across categories between cases and control. Significant factors associated with asthma in bivariate analysis were submitted to conditional multivariate logistic regression analysis. Results: Factors significantly associated with asthma were being obese (OR=5.10; 95% CI 2.09-12.42), having a history of allergic rhinitis (OR=7.10; 95% CI 3.24-15.52), born preterm (OR=6.06; 95% CI 2.05-17.87), living in a carpeted home (OR=3.06; 95% CI 1.41-6.64), using a gas stove (OR=9.09; 95% CI 3.93-21.03), playing with plush toys (OR=4.58; 95% CI 2.04-10.30), living in a home distanced less than 500 meters from the main traffic road (OR=3.68; 95% CI 1.27-10.70), less than 500 meters from a plant farm (OR=3.78; 95% CI 1.68-10.70), and less than 500 meters from an electric station (OR=5.57; 95% CI 1.73-17.93). Conclusions: This study confirms the associations between individual, outdoor-indoor environmental factors, and bronchial asthma among children in Medina. This study is a step forward into the future of interventional programs to control bronchial asthma among children.